2001
DOI: 10.2166/ws.2001.0034
|View full text |Cite
|
Sign up to set email alerts
|

Removal of arsenate from drinking water with a natural manganese oxide in the presence of competing anions

Abstract: The efficiency of arsenic removal from drinking water in adsorption processes using natural oxides may be influenced by the presence of other adsorbable anions. The present paper focuses on the study of arsenate adsorption by a natural manganese oxide. The objective is to determine which of the anions usually present in drinking water may be adsorbed: hydrogen carbonate, sulfate, chloride, nitrate, phosphate and arsenate. A kinetic batch experiment was conducted with a natural drinking water, leading to a firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This shape showed that the system was not at equilibrium. As a matter of fact, arsenic adsorption is favorable; it is described by a Langmuir isotherm with a steep slope at the origin. Thus, the arsenic breakthrough curve at equilibrium should be stiff.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This shape showed that the system was not at equilibrium. As a matter of fact, arsenic adsorption is favorable; it is described by a Langmuir isotherm with a steep slope at the origin. Thus, the arsenic breakthrough curve at equilibrium should be stiff.…”
Section: Resultsmentioning
confidence: 99%
“…Parameters were estimated as follows: K L and q max were taken from previous measurements of adsorption isotherms, D L was obtained by tracing experiments, and D e was adjusted to reach a good fitting between experimental and computed arsenic breakthrough curves.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…There are several methods for removing lead contaminant from effluents such as ion exchange, chemical precipitation, oxidation and reduction, reverse osmosis and sorption methods [6][7][8][9][10][11][12]. In the last method, different sorbents have been used such as fly ash [13], activated carbon [14], natural surface coating [15], sea nodule [16], chitosan [17][18][19], zeolites [20][21][22], clay [23][24][25], natural oxide [26,27], industrial waste [28], iron-coated sand [29], and some biosorbents [30][31][32].…”
Section: Introductionmentioning
confidence: 99%